Development of the HELO UMKM Website Based on Geomarketing Insight to Improve Digital Marketing Effectiveness through Digital Marketing Literacy and Perceived Quality - Dynda Prista; Wening Patmi Rahayu; Titis Shinta Dhewi (Journal of Economic Education and Entrepreneurship Studies, 2026)
Digital transformation is a strategic need for MSMEs, but the use of digital technology is still not optimal and rarely integrates geomarketing insights with digital marketing literacy. This study aims to develop a HELO UMKM Website based on geomarketing insight and analyze the influence of Geomarketing Insight on Digital Marketing Effectiveness by mediating Digital Marketing Literacy and Perceived Quality. The research uses the ADDIE model Research and Development (R&D) approach on 150 student business actors who will receive UM Super funding at the State University of Malang in 2025. Data were analyzed using SEM-PLS and Wilcoxon Signed Rank Test. The results of the study show that Geomarketing Insight has the potential to support Digital Marketing Effectiveness mediated by increasing Digital Marketing Literacy which strengthens Perceived Quality. The Wilcoxon test showed that there was no significant difference between the pretest and the posttest. The novelty of the research lies in the development of the HELO UMKM Website which integrates Geomarketing Insights, digital marketing literacy, and perceived quality in one website to support data-driven MSME digital marketing.